Developmental Tuning of Epigenetic Clock - Vaiserman, Alexander (Frontiers in Genetics, 2018)
Research in the field of gerontology has traditionally focused on later stages of the life cycle. Accumulating evidence, however, suggests that both the rate of age-related functional decline and the later-life health status can be programmed during early development. The central role of epigenetic mechanisms (including DNA methylation, histone modifications and regulation by non-coding RNAs) in mediating these long-term effects has been elucidated. Both rate and direction of age-associated change of epigenetic patterns (“epigenetic drift”) were shown to be largely dependent on early-life environmental conditions. Inter-individual divergences in epigenetic profiles may occur through the stochastic errors in maintaining epigenetic marks, but they can also be adaptively mediated by environmental cues. Recent cohort studies indicate that ticking rate of epigenetic clock, estimated by a DNA methylation-based methods, may be developmentally adjusted, and that individual's discrepancies between epigenetic and chronological age may be programmed early in life. In this Perspective article, recent findings suggesting the importance of early-life determinants for life-course dynamics of epigenetic drift in humans are summarized and discussed.